2009
DOI: 10.1002/pola.23527
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of four‐arm star poly(L‐lactide) oligomers using an in situ‐generated calcium‐based initiator

Abstract: Using an in situ-generated calcium-based initiating species derived from pentaerythritol, the bulk synthesis of well-defined four-arm star poly(L-lactide) oligomers has been studied in detail. The substitution of the traditional initiator, stannous octoate with calcium hydride allowed the synthesis of oligomers that had both low PDIs and a comparable number of polymeric arms (3.7-3.9) to oligomers of similar molecular weight. Investigations into the degree of control observed during the course of the polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 79 publications
(101 reference statements)
1
24
0
Order By: Relevance
“…). This is consistent with an analogous study into the polymerization of lactide using pentaerythritol and calcium hydride as the co‐initiators . In Raman spectroscopy, hydrogen gas is evident at a high wavenumber position, 4155 cm −1 , well shifted from other Raman active gases, nitrogen (2331 cm −1 ) and oxygen (1555 cm −1 ), as well as most other substances.…”
Section: Resultssupporting
confidence: 87%
“…). This is consistent with an analogous study into the polymerization of lactide using pentaerythritol and calcium hydride as the co‐initiators . In Raman spectroscopy, hydrogen gas is evident at a high wavenumber position, 4155 cm −1 , well shifted from other Raman active gases, nitrogen (2331 cm −1 ) and oxygen (1555 cm −1 ), as well as most other substances.…”
Section: Resultssupporting
confidence: 87%
“…Synthesis of star-shaped copolymer Three reaction intermediates, PTL-PLA-COOH, NH 2 -PEG-OH, and FA-PEG were synthesized as shown in Schemes 1 and 2 according to the previous reports. [20][21][22][23] The typical peaks in 1 H NMR spectrum of these macromolecules in CDCl 3 or DMSO confirmed the formation of the above reaction intermediates. PEGylation of the star PTL-PLA was prepared by introducing hydrophilic MPEG and/or HO-PEG-FA segments into hydrophobic PTL-PLA-COOH molecule.…”
Section: Resultsmentioning
confidence: 54%
“…Three reaction intermediates, PTL‐PLA‐COOH, NH 2 ‐PEG‐OH, and FA‐PEG were synthesized as shown in Schemes and according to the previous reports 20–23. The typical peaks in 1 H NMR spectrum of these macromolecules in CDCl 3 or DMSO confirmed the formation of the above reaction intermediates.…”
Section: Resultsmentioning
confidence: 90%
“…[12][13] The same compound was used in the synthesis of four-arm PLA oligomers. [14] Authors reported that the calcium compound led to some racemization. Calcium dimethoxide and in-situ generated calcium dimethoxide prepared from calcium complexes were investigated as initiators for bulk and solution ROP of lactones in mild conditions, resulting in good yields and polymers with controlled molecular weight.…”
Section: Introductionmentioning
confidence: 98%